Differences in physical activity and sedentary time in relation to weight in 8-9 year old children - Corder Kirsten; Saxton Jenny; Hill Claire; Purslow Lisa R; Wardle Jane (BMC, 2008)
Abstract Background The health benefits of physical activity for children are well established. Although objective measures of physical activity are increasingly used there is still a lack of adequate data on physical activity in children. Sex differences in physical activity have been consistently demonstrated and lower levels of physical activity in obese than non-obese children have been shown. However, differences across the whole weight spectrum have not been examined in detail. The aim of this study was to assess associations between physical activity and sedentary time across the weight spectrum in children, and to determine whether the associations differed by sex. Methods Participants in the current study were 176 boys and 169 girls aged 8-9 years old taking part in a longitudinal study of associations between eating behaviours, physical activity and weight gain during childhood. Height, weight and waist circumference were measured, and physical activity data were collected using an Actigraph model GT1M worn for 5 consecutive days. Associations between sex, weight and physical activity were analysed using linear regression models. Results Boys had higher total activity (mean difference = 119, p < 0.001) and more minutes of moderate and vigorous physical activity (MVPA) (mean difference = 25, p < 0.001) than girls. A higher percentage of boys (72%) than girls (30%) met current physical activity guidelines of 60 minutes MVPA per day. In boys, weight status significantly predicted total activity (p = 0.001) and MVPA (p = 0.001) but there were no significant associations in girls. There was no significant difference in time spent sedentary between boys and girls, and weight status did not predict sedentary time. Conclusion In boys, physical activity was progressively lower across the weight spectrum, but in girls physical activity was consistently low across all weight categories. Intervention is required prior to 8 years old to prevent weight-related declines in physical activity in boys and further research is required to determine at what age, if ever, weight related differences in physical activity are apparent in girls.